2012
DOI: 10.4172/2167-0501.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Aloe Vera Plant Extract Against Cyclophosphamide and Buthionine Sulfoximine Induced Toxicities in the Bladder

Abstract: Bladder toxicity is one of the most troublesome side effects associated with chemotherapeutic treatments of cancer involving the use of cyclophosphamide (CP) and buthionine-SR-sulfoximine (BSO). The present study was undertaken to investigate the effects of pre-treatment with an Aloe vera plant extract (AVE) on the urotoxicity induced by acute doses of CP and BSO using a Swiss albino mice model. The modulation of toxicity was evaluated by measuring lipid peroxidation (LPO), peroxide hydrogen production (H 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[ 30 ] and Rouissil and Kouidhi et al . [ 31 ] reported that hepatotoxicity observed with CPA treatment was associated with the induction of oxidative stress due to overproduction of ROS that eventually resulted in LPO of the cellular membrane. In this present study, we showed the protective effect of GA on CPA-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] and Rouissil and Kouidhi et al . [ 31 ] reported that hepatotoxicity observed with CPA treatment was associated with the induction of oxidative stress due to overproduction of ROS that eventually resulted in LPO of the cellular membrane. In this present study, we showed the protective effect of GA on CPA-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent scientific investigations on medicinal properties of AV made it worldwide novel valuable ingredient for food, cosmetic and pharmaceutical industry [7]. Leaf exudates and mucilaginous gel of Aloe possesses anti-inflammatory, antioxidant, antifungal, antibacterial, anti-arthritic, antirheumatoid [8], anticancer [9], cytoprotective, cardiac stim-ulatory and immunomodulatory activities [10]. It is used to protect against gastric ulceration, remedy against a variety of skin disorders, promotes wound healing [11].…”
Section: Introductionmentioning
confidence: 99%